(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current situation and evaluate the change in care practices among mothers with children under 5 years old suffering from otitis media after health education counseling at Da Nang Family General Hospital. Subjects and methods: A pre-post evaluation, single-group educational intervention study was conducted on 76 mothers of children under 5 years old with otitis media who were hospitalized at the Family General Hospital, Da Nang from March to April 2025. Results: After the intervention, mothers’ practices regarding the care of children under 5 years old with otitis media changed significantly compared to before the intervention (p<0.01). The average practice score was 7.64±2.12 in the pre-intervention assessment, increasing to 14.09±3.59 in the post-intervention assessment and 12.00±4.42 in the one-month post-intervention assessment. Conclusion: Mothers’ practices of caring for children under 5 years old with otitis media before the intervention was limited and was significantly improved after the health education and counseling intervention. This shows the importance of regular health education and counseling for mothers in improving the quality of care and treatment for children.